Concepts in enterprise resource planning - Monk, Ellen F.; Wagner, Bret J. (Australia ; Boston, Mass. : Course Technology Cengage Learning, 2009)
In today's cutting-edge business world, enterprise resource planning (ERP) software plays a critical role. By bringing a company's many different functions together into one large integrated system, it creates an abundance of opportunities for growth and increased productivity. However, mastery of ERP is central to success and Concepts in Enterprise Resource Planning, Third Edition, provides the perfect tool for making sense of this vastly important technology. The book examines enterprise software in general and shows readers how ERP software can improve the functions of a company, how it can streamline operations, and how the functional areas of any package relate to each other. The third edition has been updated to reflect the very latest trends and updates in ERP software. With all new sidebar cases and real-world examples throughout, this text will not only provide a thorough introduction to the world of enterprise resource planning, but will also prepare readers for success in today's marketplace.
1. Business Functions, Processes and Data Requirements -- 2. The Development of Enterprise Resource Planning Systems -- 3. Marketing Information Systems and the Sales Order Process -- 4. Production and Supply Chain Management Information Systems -- 5. Accounting in ERP Systems -- 6. Human Resources Processes with ERP -- 7. Process Modeling, Process Improvement, and ERP Implementation -- 8. ERP and Electronic Commerce.
Includes bibliographical references and index.
1
Keywords: SAP R/3.; introduction to Entrepreneurship and Small Business Management; Business & Strategic Management; Business planning; Business enterprises -- Computer networks -- Management; Information resources management